2009
DOI: 10.5858/133.11.1868
|View full text |Cite
|
Sign up to set email alerts
|

Primary Bone Lymphoma

Abstract: Primary bone lymphomas are rare, even though secondary involvement of the bone marrow is a common event in systemic lymphomas. Most primary bone lymphomas are primary bone diffuse large B-cell lymphomas (PBDLBCLs) with a rare occurrence of follicular, marginal zone, anaplastic large cell, Hodgkin, and T-cell lymphomas. The PBDLBCL affects the middle-aged to elderly population, with a slight predominance in men. The patients present with bone pain, palpable mass, fractures, or neurologic symptoms. The metaphysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 19 publications
1
22
0
Order By: Relevance
“…Meanwhile, Pfreundschuh et al [ 19 ] suggested that rituximab in combination with CHOP-like chemotherapy regimens improves the long-term prognosis of young patients with PB-DLBCL. Bhagavathi and Fu's study [ 20 ] found that the addition of rituximab increased three-year progression-free survival (PFS) from 52% to 88%. Radiotherapy used the usual doses for non-Hodgkin's lymphoma (35–45 Gy in 1.8–2 Gy fractions) [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, Pfreundschuh et al [ 19 ] suggested that rituximab in combination with CHOP-like chemotherapy regimens improves the long-term prognosis of young patients with PB-DLBCL. Bhagavathi and Fu's study [ 20 ] found that the addition of rituximab increased three-year progression-free survival (PFS) from 52% to 88%. Radiotherapy used the usual doses for non-Hodgkin's lymphoma (35–45 Gy in 1.8–2 Gy fractions) [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…The male to female ratio was 1.5 / 1. Most primary bone lymphomas are DLBCL (26). All of the cases in our series were DLBCL.…”
Section: Discussionmentioning
confidence: 54%
“…According to Bhagavathi's review, primary bone lymphoma is a rare entity; it constitutes 4-5% of ENLs and 3% of all bone malignancies (26). The 27.8% of musculoskeletal lymphomas in our series primarily occurred in the bone.…”
Section: Discussionmentioning
confidence: 61%
“…Histologically, PBL is characterised by a diffuse cellular population infiltrating bony trabeculae and medullary fat [6]. Immunohistochemical analysis confirms diffuse positivity for CD20 [2].…”
Section: Discussionmentioning
confidence: 87%